Screening for Fetal Chromosomal Abnormalities: ACOG Practice Bulletin, Number 226. Issue 4 (October 2020) - Rose, Nancy C.; Kaimal, Anjali J.; Dugoff, Lorraine; Norton, Mary E.
Abstract : Prenatal testing for chromosomal abnormalities is designed to provide an accurate assessment of a patient's risk of carrying a fetus with a chromosomal disorder. A wide variety of prenatal screening and diagnostic tests are available; each offers varying levels of information and performance, and each has relative advantages and limitations. When considering screening test characteristics, no one test is superior in all circumstances, which results in the need for nuanced, patient-centered counseling from the obstetric care professional and complex decision making by the patient. Each patient should be counseled in each pregnancy about options for testing for fetal chromosomal abnormalities. It is important that obstetric care professionals be prepared to discuss not only the risk of fetal chromosomal abnormalities but also the relative benefits and limitations of the available screening and diagnostic tests. Testing for chromosomal abnormalities should be an informed patient choice based on provision of adequate and accurate information, the patient's clinical context, accessible health care resources, values, interests, and goals. All patients should be offered both screening and diagnostic tests, and all patients have the right to accept or decline testing after counseling. The purpose of this Practice Bulletin is to provide current information regarding the available screening test options available for fetal chromosomal abnormalities and to review their benefits, performance characteristics, and limitations. For information regarding prenatal diagnostic testing for genetic disorders, refer to Practice Bulletin No. 162, Prenatal Diagnostic Testing for Genetic Disorders . For additional information regarding counseling about genetic testing and communicating test results, refer to Committee Opinion No. 693, Counseling About Genetic Testing and Communication of Genetic Test Results . For information regarding carrier screening for genetic conditions, refer to Committee Opinion No. 690, Carrier Screening in the Age of Genomic Medicine and Committee Opinion No. 691, Carrier Screening for Genetic Conditions . This Practice Bulletin has been revised to further clarify methods of screening for fetal chromosomal abnormalities, including expanded information regarding the use of cell-free DNA in all patients regardless of maternal age or baseline risk, and to add guidance related to patient counseling.